Progress of Crop in Some Rhizophora Stands before First Thinning in Matang Mangrove Reserve of Peninsular Malaysia - Srivastava, P. B. L; Guan, Saw Leng; Muktar, Ashari (1988)
The study reports the composition and growth pattern of the crops dominated by Rhizophora species in terms of stocking density, diameter and height growth in some well-managed stands in Matang Mangrove Reserve of Peninsular Malaysia. In all, 10 stands representing 6 years (4), 9 years (3) and 12 years (3) were studied. On an average there were 8371,4661 and 4181 stems/ha of Rhizophora in 6, 9 and 12 year-old crops respectively. Mean DBH and height for the respective age crops were 3.26 cm and 6.34 m, 5.50 cm and 10.96 m and 6.91 cm and 12.62 m. Highest mortalityoccu"edin 6-9 year-old crop. This period also showed best growth both in diameter and height. These studies indicate the need for silvicultural thinning in 6- 9 year-old crop. The climber Derris trifoliata may seriously affect growth and survival in some areas.